ANALISIS KINERJA SAHAM DAN PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN YANG MELAKUKAN IPO DI BURSA EFEK JAKARTA TAHUN 2000-2004 - Indriyani, Irma; Jaryono, Jaryono; Suwaryo, Suwaryo (Faculty of Economics and Business Universitas Jenderal Soedirman, 2007)
The research entitled “The Analysis of The Stocks Performance and Earnings Management Practice on Companies Issuing Initial Public Offering (IPO) at Jakarta StockExchange (JSX) Year 2000-2004” used secondary data. Hypotheses proposed in this research were : 1. The short-term stocks performance was outperformed, whereas long-term stocks performance was underperformed. 2. There was a significance gap between short-term stocks performance and long-term stocks performance. 3. There was earnings management practice one year before go public. 4. There was a significant correlation between earnings management before go public and long-term stocks performance. To test the first and second hypotheses was used statistical test such as one sample ttest and paired sample t-test of abnormal return on each observation period. Short-term stocks performance was measured by length of time such as one month and three months after IPO. Meanwhile, long-term stocks performance was measured by length of time such as 12 and 24 months after IPO.The result of statistical analysis showed that short-term stocks performance was outperformed, whereas long-term stocks performance was underperformed. This wassupported by the t calculation of one-month period (3,523) and three months periods (3,618) were bigger than t table (1,9966 and 1,9925). Meanwhile, t calculation 12 months period (-0,185) and 24 months periods (-1,861) were less than t table (1,9917 and 1,9886). The result of paired sample t-test was 4,857 on the level of significance 0,05. It showed that there was a significance gap between short-term stocks performance and longterm stocks performance. To know wether there was earnings management practice one year before go public was used discretionary accruals measurement by using Friedlan approach (1994). Then, statistical test was used as well to support the result of this research. The result of discretionary accruals measurement, Wilcoxon test, and Sign test showed that there was a signal showing earnings management practice by implementing income increasing discretionary accrual method one year before go public. To test the last hypotheses was used Pearson Product Moment Correlation test. The result showed that there was a insignificance negative correlation (-0,151) between earnings management before go public and long term stocks performance.